Association between physical activity changes and risky behaviors among adolescents and young adults in Switzerland—a longitudinal study - Dumas, Marine; Tercier, Stephane; Suris, Joan-Carles; Barrense-Dias, Yara (Health Promotion & Physical Activity, 2025)
Purpose: Recent global studies on physical activity patterns among adolescents indicate that a significant majority fail to meet recommended activity levels, with higher amounts of sedentary behavior in this age group associated with poorer behavioral outcomes. The aim of this longitudinal study is to examine physical activity (PA) changes in a cohort of 1386 15–24-year-olds youth and to evaluate their association with risky behaviours. Material and methods: Data were retrieved from the first (T1-2015-2016) and third (T3-2017–2018) waves of the GenerationFree study in Switzerland. Respondents were divided into four groups according to PA changes between T1–T3: Actives (16.2%), Increasers (11.3%), Decreasers (15.1%) and Inactives (57.4%). Results are given as relative risk ratios (RRR) using Actives as reference. Results: One in six was physically active during the studied period. Compared to Actives, Increasers (RRR 2.154) and Decreasers (RRR 1.900) were more at-risk of smoking at T3, and Inactives at T1 (RRR 1.952) and T3 (RRR 2.218). While Decreasers (RRR 0.522) and Inactives (RRR 0.507) had lower odds for alcohol misuse at T1, Decreasers had higher odds at T3 (RRR 2.092). At T3, Inactives were more at-risk of an eating disorder (RRR 1.675). No relationship was found for cannabis use or problematic Internet use. Conclusions: As PA guidelines are not met by most participants, PA should be promoted actively in adolescents by public health authorities and schools, and risk-taking should be prevent in active young people.